The prohibition of competition in employment relationship in Cameroon - Cyrille Monkam (Juridical Tribune, 2017)
The study aims to analyze one of the apparent inconsistencies that are found in the employment law in Cameroon. The right of free competition is tantamount to a free market society especially in the era of globalization. It appears prima faciae that in Cameroon the lawmaker has limited this right in the area of employment law, the reason being the protection of employers’ businesses that constitute a source of tax income in the fragile economic environment and an opportunity for job seekers. However, a close look at the provisions of Labour code shows that the law does favour on the one hand the employee right to compete on condition not to constitute a threat on the business of his current or former employer. On the other hand, the employer has to compensate his employee in case of legal non-compete clause and cannot compel him to respect illicit contractual noncompete clauses. If one of the parties to the employment contract develops such an unscrupulous behaviour, he will feel the harshness of the law. This research reveals the wish of the Cameroon lawmaker to adapt its legislation to social and economic realities.